THE METHODS SAMPELING SELECTION BOILER ENERGY EQUIPMENT - Самков, О.; Ничипоренко, Л.; Калакура, Р.; Глушков, В. (Science-based technologies, 2011)
To solve the task evaluation and sampling power boiler equipment by many parameters proposed methodologi-cal approach based on the method of analysis hierarchy.